Aztecs : an interpretation - Clendinnen,Inga (Cambridge University press, 1991)
In 1521, the city of Tenochtitlan, magnificent centre of the Aztec empire, fell to the Spaniards and their Indian allies. Inga Clendinnen's account of the Aztecs recreates the culture of that city in its last unthreatened years. It provides a vividly dramatic analysis of Aztec ceremony as performance art, binding the key experiences and concerns of social existence in the late imperial city to the mannnered violence of their ritual killings.